Open Book Examination: Struggling Learners’ Motivation and Academic Achievement in Physics at Secondary level - Tariq Javed,; Choudhary, Farkhunda Rasheed (JIE, 2020)
The learning disabilities of the struggling learners is considered as their weakness; however, it can be converted into their strength through motivation and the mechanism of open book examination. This research paper is about the struggling learner’s motivation and academic achievement. It is an experimental study where struggling learners were given the exposure of open book examination.